Persepsi Peserta Didik Kelas XI MIA 1 SMA Negeri 1 Titehena terhadap Penggunaan Laboratorium Virtual (Phet Simulation) dalam Pembelajaran Fisika pada Materi Hukum Hooke - Maria Paulina Witin; Agustina Elizabeth; Yustina Yesisanita Yeyen; Yustina Tuti Lein (Departement of Mathematics Education, 2024)
SMAN 1 Titehena is one of the high schools that has a shortage of classrooms so that the physics laboratory is used as a classroom. In addition, the practicum equipment in the physics laboratory is also incomplete. Due to the limitations of these practical tools, physics learning only takes place in the classroom and students only learn theory without ever doing practicum. This makes students feel bored and saturated when participating in physics learning. This research was conducted using qualitative methods with descriptive analysis techniques where students' perceptions were measured using a questionnaire. The results showed that the average percentage of the first indicator of the use of virtual laboratories (PhET Simulation) was 74%, the ease of use indicator of virtual laboratories (PhET Simulation) was 81%, the difficulty indicator of using virtual laboratories (PhET Simulation) was 56%. Thus it can be said that the perception of students in class XI Mia 1 SMA Negeri 1 Titehena towards the use of virtual laboratories (PhET Simulation) in learning physics on Hooke's Law material as a whole received a positive response.